Implementation of One Dimensional Finite Difference Heat Conduction Method to Quantity Heat Transfer through Lightweight Cellular Mortar - Azree Othuman Mydin, Md; Musa, Mazlina (International Journal of Engineering and Technology, 2018)
This paper accounts the origin of Finite Difference technique (one dimensional) to determine thermal performance of lightweight cellular mortar. This paper will also assimilate the execution of the technique and the reasoning of thermal properties model of lightweight cellular mortar. For this work, a one dimensional finite difference heat conduction simple excel program had been developed to foresee the temperature enlargement via the width of the lightweight cellular mortar system, based on initial approximation of the thermal conductivity properties in relation to the temperature growth in the model as a function of the cellular mortar porosity and the effect of radiation and heat emission surrounded by the voids inside the cement matrix. The accuracy of the developed simple model was then evaluated by equalling prophesied and measured temperature growth assimilated from prototype heat transfer assessment on lightweight cellular mortar system to facilitate the temperature growth of the sample premeditated by the program meticulously bouts those verified through the experimental procedure. Â Â